Insights into extrinsic foot muscle activation during a 75 min run using T2 mapping - Grischa Bratke (Nature Portfolio, 2021)
Abstract The extrinsic foot muscles are essentially for controlling the movement path but our knowledge of their behavior during prolonged running is still very limited. Therefore, this study analyzed the time-course of muscle activation using T2 mapping during 75 min of running. In this prospective study, 19 recreational active runners completed 75 min of treadmill running at a constant speed. Interleaved T2 mapping sequences were acquired and segmented at timepoints 0, 2.5, 5, 10, 15, 45, and 75 min. ANOVA for repeated measurements followed by a Tukey post hoc test and Pearson correlation between running speed and initial signal increase at 2.5 min were calculated. All muscles showed a significant signal increase between baseline and 2.5 min (e.g. medial gastrocnemius: + 15.48%; p < 0.01). This was followed by a plateau phase till 15 min for all but the extensor digitorum longus muscle and a significant decrease at 45 or 75 min for all muscles (all p < 0.05). Correlation between running speed and signal increase was negative for all muscles and significant for both gastrocnemii (e.g. medial: r =  − 0.57, p = 0.0104) and soleus (r =  − 0.47, p = 0.0412). The decrease of relaxation times times in the later running phases was less pronounced for faster runners (≥ 10 km/h). T2 relaxation times do not only decrease after cessation of exercise but already during prolonged running. The lesser initial increase and later decrease in faster runners may indicate training induced changes.